UNDERSTANDING CONSUMERS’ BOOKING INTENTION IN THE JAKARTA HOTEL INDUSTRY: A CASE STUDY OF ‘APS’ HOTEL - Gwen Evelyn Sudarto; Tommy Setiawan Ruslim (International Journal of Application on Economics and Business, 2026)
Despite the overall growth of the hospitality industry in Jakarta, the ‘APS’ Hotel has experienced declining performance that has even led to property sale considerations, highlighting the need for further investigation into consumer behavior. This study examines the influence of brand image, trust, price fairness, service quality, and perceived value on booking intention among guests of the ‘APS’ Hotel in Jakarta. A single cross-sectional design was employed, utilizing a judgmental sampling technique, with 228 respondents residing in Jakarta who had previously booked and stayed at the hotel. Data were collected in September 2025 through an online questionnaire distributed through TikTok and WhatsApp and analyzed using the PLS-SEM approach. The results indicate that all examined variables have a positive and statistically significant effect on consumers’ booking intentions toward the hotel.